EVALUATION OFANTI-OXIDANT AND ANTI-ACNE ACTIVITIES (IN-VITRO) OF THE FORMULATED HERBAL GELS - Shah, Khushbu Pravin; Srivastava, Rashmi Shukla (International Journal of Current Pharmaceutical Research, 2015)
Objective: The objective of the present study was to evaluate the anti-oxidant and anti-acne activities (in-vitro) of the formulated herbal gels. Methods: Herbal extracts and volatile oils were prepared and procured. Preliminary screenings for the anti-oxidant and anti-acne activities (in-vitro) were carried out to select the suitable candidates for the preparation of anti-acne herbal gels. Gels were further evaluated for the activities. Results: The herbal gel (F2) containing the herbal extracts (Azadirachtaindica, Ocmium sanctum, Curcuma longa) each (1%) and volatile oils (Melaleucaalternifoliae, Salviaesclareae and Citrus sinensis) each (0.05%) showed maximum anti-oxidant activity (IC50 value 0.407 mg) amongst all four gels. Significant anti-acne activity against P. acne and S. epidermidis was showed by F2 when compared with the marketed synthetic gel (Clindac gel). Conclusion: The study proves that the herbal actives used in the formulation have promising anti-oxidant and anti-acne activity.